Model dan Sistem Komunikasi Pembelajaran - Yusra Jamali; Janawi Janawi; Rada Rada (Sustainable, 2019)
Progress in information and technology simultaneously affect patterns of interaction and communication systems in education and learning. The availability of increasingly complex communication devices, is so simple that it is increasingly easy to use. Communication is a bridge to establish interactions between individuals and groups, sending messages between individuals and groups can be received directly without time difference even though far apart. The learning process as an interaction and communication is directed to help develop all the potential, skills, positive characteristics possessed by students. Learning interaction patterns and criteria can be done with basic patterns of interaction, interaction centered on content, interaction centered on the teacher, interaction centered on students, communication learning is very important in order to determine the success of education. The learning achievements of each graduate are also influenced by patterns of interaction and communication systems applied by educators. The teaching and learning process, mostly occurs because of the communication process, both which takes place intrapersonal and interpersonal. Progress an educational technology also results in the increasingly available educational devices based on optic / teleconference sources and learning materials available on the internet, media and learning tools based on visual and audio visual. Learning technology will lead to curriculum improvement, improvement of teacher / lecturer resources, improvement of graduate quality, absorption of graduates and satisfaction of alumni users. Abstrak Kemajuan informasi dan teknologi secara simultan sudah mempengaruhi pola interaksi dan sistem komunikasi pendidikan dan pembelajaran. Ketersediaan perangkat komunikasi yang semakin kompleks, sangat sederhana sehingga semakin mudah digunakan. Komunikasi merupakan jembatan untuk menjalin interaksi antara individu dan kelompok, pengiriman pesan antar individu dan kelompok dapat diterima secara langsung tanpa perbedaan waktu meskipun tempat berjauhan. Proses pembelajaran sebagai interkasi dan komunikasi diarahkan untuk membantu mengembangkan semua potensi, kecakapan, karakteristik positif yang dimiliki oleh peserta didik. Pola dan kriteria interaksi pembelajaran dapat dilakukan dengan pola dasar interaksi, interaksi berpusat pada isi, interaksi berpusat pada guru, interaksi berpusat pada siswa, komunikasi pembelajaran sangat penting dalam rangka menentukan keberhasilan pendidikan. Capaian pembelajaran setiap lulusan dipengaruhi pula oleh pola interaksi dan sistem komunikasi yang diterapkan oleh tenaga pendidik. Dalam proses belajar mengajarnya, sebagian besar terjadi karena proses komunikasi, baik yang berlangsung secara intrapersona maupun secara antarpersona. Kemajuan teknologi pendidikan juga berakibat pada semakin tersedianya perangkat pendidikan yang berbasis optic/teleconference sumber dan bahan belajar yang tersedia di intenet, media dan perangkat pembelajaran yang berbasis visual dan audio visual. Teknologi pembelajaran akan bermuara pada perbaikan kurikulum, peningkatan sumberdaya guru/dosen, peningkatakan mutu lulusan, daya serap lulusan dan kepuasan pengguna alumni.